Retrospective cohort study of clinical characteristics of 2199 hospitalised patients with COVID-19 in New York City. Issue 11 (27th November 2020) - Paranjpe, Ishan; Russak, Adam J; De Freitas, Jessica K; Lala, Anuradha; Miotto, Riccardo; Vaid, Akhil; Johnson, Kipp W; Danieletto, Matteo; Golden, Eddye; Meyer, Dara; Singh, Manbir; Somani, Sulaiman; et al.
Abstract : Objective: The COVID-19 pandemic is a global public health crisis, with over 33 million cases and 999 000 deaths worldwide. Data are needed regarding the clinical course of hospitalised patients, particularly in the USA. We aimed to compare clinical characteristic of patients with COVID-19 who had in-hospital mortality with those who were discharged alive. Design: Demographic, clinical and outcomes data for patients admitted to five Mount Sinai Health System hospitals with confirmed COVID-19 between 27 February and 2 April 2020 were identified through institutional electronic health records. We performed a retrospective comparative analysis of patients who had in-hospital mortality or were discharged alive. Setting: All patients were admitted to the Mount Sinai Health System, a large quaternary care urban hospital system. Participants: Participants over the age of 18 years were included. Primary outcomes: We investigated in-hospital mortality during the study period. Results: A total of 2199 patients with COVID-19 were hospitalised during the study period. As of 2 April, 1121 (51%) patients remained hospitalised, and 1078 (49%) completed their hospital course. Of the latter, the overall mortality was 29%, and 36% required intensive care. The median age was 65 years overall and 75 years in those who died. Pre-existing conditions were present in 65% of those who died and 46% of those discharged. In those who died, the admission median lymphocyte percentage was 11.7%, D-dimer was 2.4 μg/mL, C reactive protein was 162 mg/L and procalcitonin was 0.44 ng/mL. In those discharged, the admission median lymphocyte percentage was 16.6%, D-dimer was 0.93 μg/mL, C reactive protein was 79 mg/L and procalcitonin was 0.09 ng/mL. Conclusions: In our cohort of hospitalised patients, requirement of intensive care and mortality were high. Patients who died typically had more pre-existing conditions and greater perturbations in inflammatory markers as compared with those who were discharged.